Assessment of the spermatozoa transports between porous cervical walls continuously secreting Jeffrey fluid in human cervical canal - Walait, Ahsan; Siddiqui, A. M.; Rana, M. A.; Ashraf, H.; Shah, Nehad Ali; Jeon, Yongseok (Alexandria Engineering Journal, 2024)
Understanding spermatozoa transportation in the human female cervical canal, particularly in relation to the fertilization process, holds significant physiological importance. Present paper accords with the assessment of the self-propelling sheet of spermatozoa (SPSS) between porous cervical walls continuously secreting viscoelastic mucus in the human cervical canal (HCC). Mathematical modelling of the biological model yielded two inhomogeneous partial differential equations. These partial differential equations along with Saffman slip conditions are solved for exact solutions. It is delineated that an increase in the Reynolds number, Jeffrey parameter, and slip parameter results in an increase in the propulsive velocity and mucus velocity. Conversely, an increase in Darcy number results in a decrease in both propulsive and mucus velocity. When the secreting velocity is constant, the propulsive velocity is maximal, and when the secreting velocity is exponential, it is minimal. Spermatozoa move through the Jeffrey fluid more quickly than they do in the Newtonian fluid. The propulsive velocity through the channel is higher than in unbounded domain. The propulsive velocity of the spermatozoa in cervical canal is approximately 80μm/s in particular environment.
Keywords: Biological models; Cervical canal; Fertilisation; Jeffreys fluids; Permeable wall; Saffman slip condition; Slip condition; Spermatozoon transport; Swimming sheet; Viscoelastics; Cervical canal; Jeffrey fluid; Permeable walls; Saffman slip condition; Spermatozoa transport; Swimming sheet